IMPROVING AESTHETIC TRAINING OF 5TH GRADERS ON THE BASIS OF NATIONAL EMBROIDERY - Olimova Dilnoza Murodullo qizi (American Journals Publishing, 2023)
This thesisalso discusses the methodology of aesthetic training based on teaching national embroidery samples to 5th graders in teaching, integrating its history and some aspects.
Keywords: Embroidery, craftsmanship, technology, methods, efficiency.